Pharmacokinetic and Biomarker Quantification Studies on Vancomycin-Loaded PEGylated Liposomes and Its Potential to Reduce Vancomycin-Induced Kidney Injury: A Rat Study - Medha D. Joshi; Paulina Iacoban; Marc H. Scheetz (MDPI AG, 2023)
Vancomycin is a commonly used antibiotic in hospital settings, especially against Methicillin-resistant staphylococcus aureus (MRSA). One of the major adverse events of vancomycin use in adults is kidney injury. The drug concentration, specifically the area under the concentration curve, predicts kidney injury in adults receiving vancomycin. To attempt to reduce vancomycin-induced nephrotoxicity, we have successfully encapsulated vancomycin in polyethylene glycol-coated liposomes (PEG-VANCO-lipo). We have previously carried out in vitro cytotoxicity studies on kidney cells using PEG-VANCO-lipo and found it to be minimally toxic compared to the standard vancomycin. In this study, we have dosed male adult rats with PEG-VANCO-lipo or vancomycin HCl and compared plasma vancomycin concentrations and KIM-1 as an injury biomarker in rat urine. Male Sprague Dawley rats (350 ± 10 g) were administered vancomycin (n = 6) or PEG-VANCO-lipo (n = 6) 150 mg/kg/day for three days using an IV infusion in the left jugular vein catheter. Blood was collected for plasma at 15, 30, 60, 120, 240, and 1440 min after the first and the last IV dose. Urine was collected 0-2, 2-4, 4-8, and 8-24 h after the first and the last IV infusions using metabolic cages. The animals were observed for three days after the last compound administration. Vancomycin was quantified in plasma by LC-MS/MS. Urinary KIM-1 analysis was done by using an ELISA kit. Three days after the last dose, under terminal anesthesia with IP ketamine (65-100 mg/kg) and xylazine (7-10 mg/kg), rats were euthanized. Vancomycin urine and kidney concentrations and KIM-1 were lower on day three in the PEG-Vanco-lipo group compared to the vancomycin group (p < 0.05, ANOVA and/or t-test). There was a significant reduction in plasma vancomycin concentration on day one and day three (p < 0.05, t-test) in the vancomycin group compared to the PEG-VANCO-lipo group. Vancomycin-loaded PEGylated liposomes resulted in lower levels of kidney injury, as noted by a decrease in KIM-1 values. Moreover, longer circulation in plasma with increased concentration in plasma as opposed to the kidney was observed with the PEG-VANCO-lipo group. The results indicate the high potential of PEG-VANCO-lipo in decreasing the nephrotoxicity of vancomycin clinically.